Reformulating Conservation Policies For Indigenous Peoples In Indonesia - Muhammad Arsyad; Imam Koeswahyono; Indah Dwi Qurbani (The Islamic Education and Multiculturalism Foundation, 2025)
The conservation of biological natural resources and ecosystems in Indonesia is still characterized by a centralized and state-dominated approach, as regulated by Law No. 5 of 1990 and Law No. 32 of 2024. This centralized system marginalizes Indigenous Peoples (Masyarakat Hukum Adat, or MHA), disregarding their local wisdom, such as sasi in Maluku and customary forest management by Dayak communities. While the new legislation mentions the involvement of MHA, their role remains symbolic, lacking meaningful participation or authority. This research aims to identify the gaps in conservation regulations concerning MHA and to formulate a progressive policy reform based on the principle of greatest happiness, derived from Bentham's utilitarianism and Satjipto Rahardjo's progressive legal theory. Using a normative juridical method and qualitative analysis, the study finds that legal inconsistencies, overlapping regulations, and tokenism contribute to ecological and social injustice. The study proposes a policy reform framework based on four pillars: recognition of customary law, full decentralization of conservation governance to MHA, mandatory application of Free, Prior, and Informed Consent (FPIC), and fair benefit-sharing mechanisms. The proposed model, integrating Indigenous Self-Governance and Full Community-Based Conservation, strengthens legal certainty and justice, reflecting a human-centered and sustainable legal approach. Successful indigenous conservation practices, such as in Sungai Utik and Wehea Forest, illustrate the viability of this model.